Performance of irrigated green corn cultivars in different plant populations at sowing - Soares Neto, José C.; Santos Neto, Antônio L. dos; Santos, Wellington M. dos; Barros, Daline T. S.; Souza, Ademária A. de; Albuquerque Neto, João C. de (Revista brasileira de engenharia agrícola e ambiental, 2017)
ABSTRACT This study aimed to evaluate the yield of green corn hybrids grown under irrigation in different plant populations at sowing. The assay was carried out in the experimental area located in the city of Arapiraca, Alagoas State, Brazil, from November 2015 to January 2016. A randomized complete block design (RCBD) was used, in a 2 x 5 factorial scheme with four replicates. A double- and a single-cross hybrid (AG 1051 and BM 3061), which are suitable for green corn production, were cultivated in five spacings between plants at sowing (15.0, 17.5, 20.0, 22.5 and 25.0 cm). The characteristics photosynthetic rate (PR), ear length with rusk (HEL) and without husk (UEL), husked ear weight (HEW), unhusked ear weight (UEW), percentage of marketable ears (%ME) and weight of husk (HW) were evaluated. The double- and single-cross hybrids AG 1051 and BM 3061 showed green ears with commercial standard. The cultivar BM 3061 showed the best results for most of the characteristics related to the performance of green corn (PR, HEL, UEL, UEW, HEW, %ME). The spacing of 17.5 cm between plants at sowing was the most indicated for irrigated green corn cultivation. RESUMO O trabalho objetivou avaliar a produtividade de híbridos de milho-verde sob irrigação cultivados em diferentes populações de plantas na semeadura. Foi conduzido na área experimental localizada no município de Arapiraca, AL, no período de novembro de 2015 a janeiro de 2016. O delineamento experimental utilizado foi em blocos casualizados, em esquema fatorial 2 x 5, com quatro repetições. Foram analisados dois híbridos, duplo e simples, indicados para milho verde (AG 1051 e BM 3061) e cinco espaçamentos entre plantas na semeadura (15,0; 17,5; 20,0; 22,5 e 25 cm). Foram avaliadas as características: taxa fotossintética (TF), comprimento de espigas com palha (CECP) e sem palha (CESP), peso de espigas com palhas (PECP) e sem palhas (PESP), porcentagem de espigar comerciais (%EC) e peso da palha (PP). Os híbridos duplo e simples, 1051 e BM 3061, apresentam espigas verdes com padrão comercial. A cultivar BM 3061 possui melhor desempenho para a maioria das características relacionadas ao desempenho da cultura (TF, CECP, CESP, PP, PECP, PESP, %EC). O espaçamento de 17,5 cm entre plantas na semeadura mostrou-se mais indicado para o cultivo do milho-verde irrigado.